2021
DOI: 10.1111/tmi.13687
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Health Series – Alcohol, tobacco, and other drug use among adolescents in sub‐Saharan Africa: A narrative review

Abstract: Alcohol, tobacco, and other drug (ATOD) use by adolescents are major contributors to death and disability in sub-Saharan Africa (SSA). This paper reviews the extent of adolescents' ATOD use, risk and protective factors, and studies evaluating prevention interventions for adolescents in SSA. It also describes the harms associated with adolescents' ATOD use in SSA, which mainly include interpersonal violence, sexual risk behaviours, and negative academic outcomes. We use the socio-ecological model as our framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…Also, the smoking habit is influenced by a myriad of factors including financial ability to purchase a cigarette, peer pressure, psychological instability, strictness on smoking regulations, societal cultures, etc. 22 hence; more studies are needed to understand the relationship between SEC and smoking in adolescents in Lagos, Nigeria. In this study, only 37% of respondents had previously utilized the dental clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the smoking habit is influenced by a myriad of factors including financial ability to purchase a cigarette, peer pressure, psychological instability, strictness on smoking regulations, societal cultures, etc. 22 hence; more studies are needed to understand the relationship between SEC and smoking in adolescents in Lagos, Nigeria. In this study, only 37% of respondents had previously utilized the dental clinic.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] No reviews in LMICs or SSA have focused on AUDs among YPLH, yet initiation of regular drinking occurs in childhood and adolescence regardless of HIV status. 10 A previous review, conducted in 2013 in Eastern Africa among young people aged 15-24 years, reported the prevalence of alcohol use in the past 1 month to be 28%, the past 1 year prevalence to be 26% 11 and the median prevalence of lifetime use to be 52%. This means that one in two young people in Eastern Africa has ever used alcohol, one in four has used alcohol in the last month, and one in four has used it in the last year.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…However, 57% of street children reported facing sexual abuse on the street. Combats, sexual violence, and sexual aggravation are among the types of offenses faced by these helpless children, and older street children are more likely to report physical aggression (Kabwela, 2020;Morojele, Ramsoomar, Dumbili, & Kapiga, 2021).…”
Section: Street Children In Zambia and Tanzania (Sub-saharan Africa)mentioning
confidence: 99%